The intracranial Windkessel implies arteriovenous pulsatile coupling increased by venous resistances. (January 2022) - Baselli, Giuseppe; Laganà, Maria Marcella
Highlights: A 2-element Windkessel model, modified for the intracranial compartment is proposed. The model added an arteriovenous capacitive coupling enhanced by venous resistances. Venous resistance was shown to enhance such coupling and venous pulsatility. In venous insufficiency, abnormal pulsatility can play a role in brain damage. Abstract: Various detailed models of cerebral circulation have been proposed, recently fostered by the hypothesized relationship between extracranial venous drainage impairment and neurodegenerative diseases. However, some basic model is missing, analogous to the 2-element Windkessel (WK) of the systemic circulation. This theoretical study focuses, in the simplest way, on the dependence of intracranial venous pressure (VP) pulsatility on the intracranial arterial 2-element WK and the venous resistance R V . The WK compliance is shown to exert an arteriovenous capacitive coupling (AV-CC), agumented by R V increments. The WK was estimated based on the intracranial arterial pressure (AP) and flow (ФICA ) waves of an open database of 3325 virtual subjects. A normal R V was estimated imposing a mean VP of 10 mmHg, doubled to mimic hindered extracranial veins. The AP to VP transfer function showed: i) a gain almost proportional to R V ; ii) a zero slightly below heart rate (HR) corresponding to the arterial WK pole; iii) a mid-frequency derivative band up to the AV-CC pole, the frequency of which was almost inversely proportional to R V ; iv) full coupling at high frequencies, yet above the pulse harmonic content, at normal HR. In conclusion, besides the well-known effect of venous hindering on the mean VP, the results of this model support the hypothesis that abnormal pulsatility of cerebral veins may play a significant role in cerebrovascular imbalance and related neurodegeneration.